1992
DOI: 10.1210/endo.130.6.1317787
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular cloning of a complementary deoxyribonucleic acid encoding the thyrotropin-releasing hormone receptor and regulation of its messenger ribonucleic acid in rat GH cells.

Abstract: Rat pituitary GH cells have been used extensively to study the biochemical actions of TRH on lactotropic cells. To investigate the structure and regulation of the rat TRH receptor (rTRHR), we have cloned its cDNA from GH4C1 cells. Using the polymerase chain reaction with degenerate primers and pools of cloned cDNAs from a GH4C1 cDNA library, a fragment sharing high similarity to the mouse thyrotrope TRHR (mTRHR) was identified. Conventional library screening with this fragment was used to isolate a single cDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…R38/B12 polyclonal Igs likely con tain antibodies of the Ab2p type that is Ab2 possessing internal images of TRH at their surface [45], Several subcellular localizations were found for the immunoreactive material. The localization observed at the cell periphery and plasma membrane level is consistent with the local ization expected for a protein belonging to the seven transmembrane receptor family [5]. However, intracytoplasmic immunofluorescent staining was also detected by confocal microscopy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…R38/B12 polyclonal Igs likely con tain antibodies of the Ab2p type that is Ab2 possessing internal images of TRH at their surface [45], Several subcellular localizations were found for the immunoreactive material. The localization observed at the cell periphery and plasma membrane level is consistent with the local ization expected for a protein belonging to the seven transmembrane receptor family [5]. However, intracytoplasmic immunofluorescent staining was also detected by confocal microscopy.…”
Section: Discussionsupporting
confidence: 85%
“…the first neuro peptide isolated from the hypothalamus, was initially dis covered as a hypophysiotropic releasing factor which causes the acute release of thyrotropin (TSH) and prolactin (PRL) [ 1 ]. It was then shown to be widely distributed in the central and peripheral nervous system and is believed to act as a neurotransmitter or neuromodulator [1], Taking advantage of clonal GH cell strains as a homogeneous pop ulation of target cells, TRH binding sites have been exten sively characterized using [3H]TRH and [3H](3Me-His)-TRH [2], Moreover, it was also shown that the TRH recep tor (TRH-R) is linked to the inositol phospholipid-cal cium-protein kinase C transduction pathway via a G aq/ al 1 protein [3], On the other hand, the cDNAs encoding the TRH-R was cloned from mouse pituitary' thyrotropes (mTRH-R) [4] and from rat GH PRL cells (rTRH-R) [5]. The deduced sequences of the corresponding proteins (393 amino acids for the mTRH-R and 412 amino acids for the rTRH-R) predict the existence of seven transmembrane domains, consistent with a G-protein-linked receptor.…”
Section: Introductionmentioning
confidence: 99%
“…4B) (43). Another network member is thyrotropin releasing hormone receptor (Trhr), which is important for the production of TSH and PRL in the pituitary gland (95). Increased Nr5a1 expression leads to increased transcription of Tpit and Nr0b1 (nuclear receptor subfamily 0, group B, member 1), also known as Dax1, which can have either antagonistic (51,94) or cooperative relationships with Nr5a1 depending on the context (67).…”
Section: -D) Tpit Immunoreactivity Was Also Unaffected (E-h) Nr5a1 mentioning
confidence: 99%
“…To date, five types of TRH receptor complementary DNAs (cDNAs) have been cloned from mammals, two isoforms from the mouse (9, 10) and two isoforms from the rat (11)(12)(13) and human (14 -16), but not in any other vertebrate classes. The structure of the TRH receptors reveals that the receptor is a member of the G protein-coupled receptor (GPCR) family.…”
mentioning
confidence: 99%